THE IMPACT OF THE ELECTRICAL INSTALLATION REGULATIONS, 2009, ON THE SALE AND LEASE OF IMMOVABLE PROPERTY - Henk Delport (Obiter, 2021)
The Electrical Installation Regulations, 2009, made by the Minister of Labour in terms of section 43 of the Occupational Health and Safety Act 85 of 1993 constitute yet another attempt on the part of the South African authorities to regulate the installation and use of electrical installations in buildings. The Regulations, published in terms of R 242 in Government Gazette 31975 of 6 March 2009, supersede the Electrical Installation Regulations, 1992, made by the Minister of Manpower in terms of section 35 of the Machinery and Occupational Safety Act 6 of 1983. They came into operation on 1 May 2009, with the exception of regulation 5(6) which took effect on 1 April 2010. The 2009 Regulations, like those they replace, impose certain substantive duties on users, lessors and installers of electrical installations. Of particular importance for property owners and lessors is the responsibility for the electrical installation on a property, and the duty to have a valid certificate of compliance in respect of such installation. The old Regulations did not describe these responsibilities and duties in clear terms, resulting in considerable confusion and uncertainty. Disappointingly, the new Regulations are only marginally better in this regard. The Department of Labour has published explanatory notes on the Regulations, but they do little more than merely citing each regulation and stating that it is selfexplanatory. The Regulations were preceded by a number of drafts which, reportedly, elicited “acrimonious debate”, even the possibility of litigation involving the Electrical Contractors’ Association of South Africa and the Department of Labour. However, the main points of dispute were not so much the impact of the Regulations on the sale and lease of immovable property but revolved around issues affecting the electrical contracting industry and its stakeholders. This note focuses on the requirements to be met in terms of the Electrical Installation Regulations, 2009, in relation to the sale and lease of immovable property, residential premises in particular. To place the discussion in perspective it is firstly necessary to examine briefly the objective and scope of the Regulations, having regard to certain key definitions contained in the Occupational Health and Safety Act and the Regulations. Any word or expression to which a meaning has been assigned in the Act has the same meaning for the purposes of the Regulations.